Decision Making Process of SMEs For Using Social Media Marketing In Industrial Revolution 4.0 - Adhania Andika Prayudanti; Devi Urianty Miftahul Rohmah (Journal of Economics, Business, and Government Challenges, 2018)
Digital era is a characteristic of Industrial Revolution 4.0 that influence towards all aspect of human life. Social media marketing is considered to be one of the technologies in the digital era that can facilitate SMEs to do business activities especially marketing activities, customer relationship, promotion, and innovation. The importance of social media marketing in digital era that its technology easy to use and need low cost. It can be applied in our smartphone, can effectively communicate with customer for promotion and branding. The aim of this paper is to define whether SMEs urgently need social media marketing in industrial revolution 4.0. This paper will review the aspects that can be motivate and disruptions of SMEs using social media marketing. The advantage of social media marketing is one of the case that can motivate SMEs using social media marketing.Meanwhile the trust and lack of the ability to using social media marketing can be disruption.